Chromosomes of Bromus auleticus Trin. ex Nees (Poaceae) - Gilmar Efrem Martinello; Maria Teresa Schifino-Wittmann (Genetics and Molecular Biology, 2003)
The chromosome number of 14 accessions of Bromus auleticus Trin. ex Nees, native of Rio Grande do Sul, was 2n = 6x = 42, same ploidy level found in other South-American Bromus species. Its chromosomes were metacentric or submetacentric, ranging from ca. 4 mm to ca. 8 mm in length. Up to two satellite-bearing chromosome pairs were sometimes observed. However, as already reported for other species, the high symmetry and homogeneity of the karyotypes made it difficult to detect possible intraspecific differences.